Composite material and its manufacturing method

By unevenly distributing thermally conductive particles between island-like resin portions, the composite material achieves high thermal conductivity and cost-effectiveness, addressing the thermal management challenges of high-density electronic devices.

JP7658234B2Active Publication Date: 2025-04-08KK TOYOTA CHUO KENKYUSHO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021158695
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-29
Publication Date
2025-04-08
Estimated Expiration
2041-09-29

AI Technical Summary

Technical Problem

Existing composite materials with high thermal conductivity, such as those using spherical diamond and flaky hexagonal boron nitride in silicone resin, achieve only a few W/mK in overall thermal conductivity, which is insufficient for high-density electronic devices.

Method used

A composite material is developed with thermally conductive particles unevenly distributed between island-like resin portions, forming a main thermal conduction path and achieving high thermal conductivity while reducing the amount of thermally conductive particles, thus lowering costs and maintaining flexibility.

Benefits of technology

The composite material exhibits high thermal conductivity (10 W/mK or more) with a reduced amount of thermally conductive particles, effectively addressing the thermal management needs of high-density electronic devices while maintaining cost-effectiveness and flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658234000001
    Figure 0007658234000001
  • Figure 0007658234000002
    Figure 0007658234000002
  • Figure 0007658234000003
    Figure 0007658234000003
Patent Text Reader

Abstract

To provide a composite material which can achieve both of suppression of an amount of heat conductive particles and high heat conductivity.SOLUTION: A composite material is composed of a resin and heat conductive particles having heat conductivity higher than that of the resin. The resin has a granular island-like part. The island-like part is preferably larger than the heat conductive particles. The heat conductive particles are unevenly distributed between the island-like parts. The heat conductive particles are preferably flat or fibrous. The heat conductive particles occupy, for example, 5-65 vol.%, with respect to the whole composite material. The island-like part occupies, for example, 30-80%, with respect to the whole cross-sectional area of the composite material. The resin preferably has an interposed part between the island-like parts. The interposed part occupies, for example, 1-10%, with respect to the whole cross-sectional area of the composite material. The composite material is obtained, for example, by pressurizing and molding a mixture of a granular resin and heat conductive particles while heating the mixture.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite material having excellent thermal conductivity. [Background technology]

[0002] Electronic devices (semiconductor modules, etc.) that have become highly dense and have high performance require heat dissipation to maintain their functions, life span, etc. Heat dissipation from electronic devices is usually achieved through heat dissipation components (heat sinks, housings, etc.) made of metal, etc. In this case, heat dissipation sheets (thermal conductive sheets, thermally conductive insulating sheets, etc.) that absorb unevenness and undulations between the electronic device (heat source) and the surfaces of the heat dissipation components are often inserted.

[0003] The heat dissipation sheet uses, for example, a composite material (including a composition) made of a filler with high thermal conductivity and a resin (including elastomer, rubber, etc.) with excellent flexibility (elasticity) and adhesion. Various proposals have been made regarding such composite materials, and for example, there are related descriptions in the following patent documents. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2016-255055 Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 proposes an isotropic, highly thermally conductive, electrically insulating composition in which spherical diamonds (first filler) and flaky hexagonal boron nitride (second filler) are dispersed in silicone (resin). Although the composition (composite material) uses a large amount of expensive diamonds with high thermal conductivity, the thermal conductivity of the entire composition remains at a maximum of several W / mK.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a new composite material etc. having excellent thermal conductivity. [Means for solving the problem]

[0007] As a result of intensive research by the inventors to solve this problem, instead of dispersing the thermally conductive particles (filler) uniformly in the resin (matrix) as in the past, they changed their approach and succeeded in obtaining a composite material with excellent thermal conductivity by unevenly distributing (aggregating, consolidating, etc.) the thermally conductive particles between island-like resin parts. By expanding on this result, they have completed the present invention, which will be described below.

[0008] 《Composite material》 (1) The present invention provides a composite material comprising a resin and thermally conductive particles having a higher thermal conductivity than the resin, the resin having granular island portions, and the thermally conductive particles being unevenly distributed among the island portions.

[0009] (2) The thermally conductive particles according to the present invention are unevenly distributed (crowded, aggregated) between granular island-shaped parts, and the island-shaped parts are likely to be in close proximity or contact with each other. It is believed that the main thermal conduction path is formed by such connections between the thermally conductive particles, and as a result, the composite material of the present invention exhibits high thermal conductivity. Furthermore, according to the composite material of the present invention, the thermal conduction path is efficiently formed due to the uneven distribution of the thermally conductive particles, so that excellent thermal conductivity can be achieved while suppressing the amount of thermally conductive particles. The reduction in the amount of thermally conductive particles not only reduces the cost of raw materials, but also reduces the overall elastic modulus (Young's modulus). Therefore, according to the present invention, a composite material with excellent thermal conductivity or flexibility (adhesion) can be provided at low cost.

[0010] <<Manufacturing method of composite material>> The present invention can also be understood as a method for manufacturing a composite material. For example, the composite material as described above can be obtained by a manufacturing method including a molding step of pressurizing and molding a mixture of a resin raw material and a thermally conductive particle raw material. The resin raw material may include at least a granular resin that forms an island-shaped portion. The mixture may be in a solid-liquid coexistence state in which a part of the resin raw material is softened or melted. In addition, a heating step of at least heating the mixture may be performed before or during the molding step.

[0011] <Heat dissipation components> The present invention can also be understood as a heat dissipation member made of the above-mentioned composite material. The heat dissipation member may be a bulk composite material processed (sliced, cut, cut, etc.) into a specific shape (sheet, block, etc.), or may be integrally molded into a desired shape by compression molding, injection molding, etc. The heat dissipation member used in electronic devices, etc. may be a thermally conductive insulating member.

[0012] "others" (1) In this specification, the term "material" means "material" or "component." Composite materials include composite materials (raw materials, etc.) with indefinite shapes as well as composite members that have been molded or processed into specific shapes.

[0013] As used herein, "resin" (including resin raw materials) includes elastomers, rubbers, etc. Such resins may be thermoplastic or thermosetting.

[0014] (2) In this specification, "x to y" includes a lower limit value x and an upper limit value y unless otherwise specified. Any numerical value included in the various numerical values ​​or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". In this specification, "x to y μm" means x μm to y μm unless otherwise specified. The same applies to other units (MPa, W / mK, Ωm, etc.). [Brief description of the drawings]

[0015] [Figure 1A] 1 is an SEM image of a composite material according to Sample 1. [Figure 1B]1 is an SEM image of the composite material of sample 2. [Figure 1C] 1 is an SEM image of the composite material of Sample 3. [Diagram 2] This is an SEM image of the composite material used to calculate the aspect ratio of the thermally conductive particles. [Diagram 3] 1 is a bar graph comparing the thermal conductivity of an unevenly distributed sample and a uniform sample. [Figure 4A] 1 is an SEM image of the composite material of Sample 4. [Figure 4B] 1 is a bar graph showing the thermal conductivity of Sample 4. [Diagram 5] FIG. 2 is a schematic diagram showing a contact or intimate state of filler (thermally conductive particles) in a matrix (resin). [Figure 6] FIG. 4 is a schematic diagram showing the change in the spacing between fillers (thermal conductive particles) depending on the presence or absence of island-shaped portions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] One or more components selected arbitrarily from this specification may be added to the components of the present invention. The contents described in this specification apply not only to composite materials (materials, members, etc.) but also to their manufacturing methods, etc. as appropriate. Even method-related components can become product-related components. Which embodiment is best depends on the target, required performance, etc.

[0017] <Heat conductive particles (raw material)> (1) Form The thermally conductive particles may be in any form that allows them to be unevenly distributed between the island-like portions of the resin. For example, when observing a cross section of the composite material, the average minimum dimension of the thermally conductive particles may be smaller than the average minimum dimension of the spacing between the island-like portions. The average minimum dimension may be determined, for example, as the arithmetic mean value of the minimum dimensions of the objects in a randomly selected predetermined area (e.g., 440 μm × 630 μm) of the cross section.

[0018] In this specification, each arithmetic mean value may be calculated for all the particles in a predetermined area, or may be calculated for 5 to 100 particles, 10 to 50 particles, or even 15 to 30 particles randomly sampled from the predetermined area (hereinafter the same). Measurements and calculations based on observed images may be performed using image processing software (e.g., ImageJ) (hereinafter the same).

[0019] The thermally conductive particles may further have a shape that allows (and facilitates) crowding, aggregation, orientation, etc. between the island-shaped portions. For example, the thermally conductive particles may be flat (scale-like, plate-like, etc.) or fibrous. As an index of such a shape, the thermally conductive particles may have an average aspect ratio (AR) of 2 to 300, 5 to 100, or even 20 to 50. If the average aspect ratio is too small (for example, substantially spherical), the gaps between the thermally conductive particles increase, and the packing, crowding or contact, orientation, etc. of the thermally conductive particles between the island-shaped portions may decrease. The average aspect ratio may be large, but the thermally conductive particles with an excessively large aspect ratio are difficult to handle.

[0020] The average aspect is determined, for example, as the arithmetic mean value of the aspect ratios of objects in a predetermined area (e.g., 440 μm × 630 μm) of a randomly sampled cross section (particularly the cross section of an interposed portion). The aspect ratio is the ratio between the longitudinal length measured for each object and the length in the direction perpendicular to the longitudinal length (longitudinal length / orthogonal length). The longitudinal length is the maximum length of the object (thermal conductive particle) (maximum length of a line segment).

[0021] The average aspect ratio is calculated based on the measured values ​​of each thermally conductive particle in the composite material, or it may be the average aspect ratio of the thermally conductive particles (single particles) at the raw material stage (before mixing with the resin raw material). For example, for flat thermally conductive particles (such as BN particles), the average aspect ratio (average particle size / average thickness) calculated based on the average thickness and average particle size may be used.

[0022] The thermally conductive particles may be smaller than the islands of the resin, for example. For example, when observing a cross section of the composite, the average maximum dimension of the thermally conductive particles may be smaller than the average maximum dimension of the islands. The average maximum dimension may be determined, for example, as the arithmetic mean value of the maximum dimensions of objects in a randomly selected predetermined area (e.g., 440 μm×630 μm) of the cross section.

[0023] (2)Content ratio The thermally conductive particles are contained in the entire composite material in an amount of, for example, 5 to 70 volume %, 15 to 65 volume %, 30 to 60 volume %, or even 40 to 55 volume %. If the amount of thermally conductive particles is too small, the thermal conductivity of the composite material may decrease. On the other hand, the more the amount of thermally conductive particles, the higher the thermal conductivity of the composite material may be, but an increase in the amount of expensive thermally conductive particles increases the manufacturing cost of the composite material. According to the present invention, the thermal conductivity of the composite material can be improved while suppressing the content of the thermally conductive particles. The volume fraction of the thermally conductive particles is not measured directly, but is calculated from, for example, the mass ratio (mixture mass ratio) of the resin and the thermally conductive particles and the true density of each.

[0024] (3) Type The type (material, manufacturing method, etc.) of the thermally conductive particles is not limited as long as the above-mentioned form is satisfied. Examples of thermally conductive particles include silica (SiO2), alumina (Al2O3), aluminum nitride (AlN), and boron nitride (BN). Among them, boron nitride has a higher thermal conductivity than silica or alumina, and is more chemically stable than aluminum nitride. Therefore, by using thermally conductive particles made of boron nitride, a composite material (thermal conductive member) with excellent thermal conductivity, heat resistance, long-term reliability, electrical insulation, etc. can be obtained.

[0025] Incidentally, boron nitride generally has a hexagonal normal pressure phase (also referred to as "h-BN" where appropriate) and a cubic high pressure phase (also referred to as "c-BN" where appropriate). h-BN is made of scales (flat with a high aspect ratio) in which hexagonal mesh layers similar to graphite are laminated, and has thermal conductivity anisotropy in which the thermal conductivity differs greatly between the surface direction (a-axis direction) and the thickness direction (c-axis direction). By orienting the surface direction of the h-BN particles in a specific direction (for example, from the heat source side to the cooling source side), the thermal conductivity (heat dissipation, etc.) of the composite material can be further increased. For this reason, thermally conductive particles made of h-BN (simply referred to as "BN particles") are usually used as a filler. However, the thermally conductive particles may also include c-BN particles and other types of particles (ceramic particles, metal particles, etc.).

[0026] The BN particles have an average particle size of, for example, 1 to 100 μm, 10 to 60 μm, 14 to 40 μm, or 18 to 30 μm. The average thickness is, for example, 0.01 to 5 μm, 0.15 to 4 μm, 0.3 to 3 μm, 0.5 to 2.5 μm, or 1 to 2 μm. BN particles of a desired size tend to aggregate, crowd, or orient between the islands of the resin, and can contribute to improving the thermal conductivity of the composite material.

[0027] The particle size and thickness of the BN particles in the composite material are determined as the arithmetic mean value of each dimension of the object in a predetermined area (e.g., 440 μm × 630 μm) of the above-mentioned cross section. In the case of BN particles (thermal conductive particle raw material, usually powder) before mixing with the resin raw material, the average particle size may be specified as the 50% diameter (D50: median diameter) from the particle size distribution obtained by the laser diffraction method. Also, the average thickness may be specified as the arithmetic mean value of the thickness measured for BN particles randomly extracted (e.g., 10 to 100 particles) from a microscope image of the powder.

[0028] 《Resin (raw material)》 (1) The resin forms islands and holds (supports) the thermally conductive particles. The islands may occupy, for example, 30 to 80%, 35 to 70%, 40 to 60%, or even 45 to 55% of the total cross-sectional area of ​​the composite. The area ratio of the islands may be calculated, for example, by image processing a predetermined region (e.g., 440 μm × 630 μm) of the observed image (cross section).

[0029] When there are resin intervening portions between the island-shaped portions, the intervening portions may occupy, for example, 1 to 10%, 2 to 8%, 3 to 6%, or even 4 to 5% of the total cross-sectional area of ​​the composite material. The area ratio of the intervening portions can be calculated, for example, by image processing a predetermined region (e.g., 50 μm × 50 μm) between the island-shaped portions of the observed image (cross section).

[0030] The island portions are preferably larger than the thermally conductive particles. For example, as described above, the average maximum dimension of the island portions is preferably larger than the average maximum dimension of the thermally conductive particles when a cross section of the composite material is observed.

[0031] (2) The resin may be of a single type or multiple types. If a single type of resin is used, the raw material mix and manufacturing process can be simplified. If multiple types of resin are used, it is possible to allocate suitable resins to the island portions and the intervening portions, taking into consideration the characteristics of each resin (thermal conductivity, wettability with thermally conductive particles, softening point, melting point, etc.).

[0032] Resins (including rubber, elastomers, etc.) are appropriately selected according to the specifications of the composite material (insulation, thermal conductivity, moldability, etc.). As the resin, synthetic resins (and even polymers) that are polymeric compounds are usually used. The resin may be either a thermoplastic resin or a thermosetting resin. Examples of thermoplastic resins include polystyrene, polymethyl methacrylate (polymethyl methacrylate / PMMA), polycarbonate, polyphenylene sulfide, etc. Examples of thermosetting resins include epoxy resins, phenolic resins, silicone resins, etc.

[0033] The elastomer may be, for example, a thermoplastic elastomer such as an olefin-based (TPO), polystyrene-based (TPS), polyvinyl chloride-based (TPVC), polyurethane-based (TPU), polyester-based (TPC), polyamide-based (TPAE), etc. The rubber may be, for example, an ethylene-propylene-diene rubber (EPDM), butyl rubber, etc., or a thermosetting elastomer (urethane rubber, silicone rubber, fluororubber, etc.).

[0034] (3) It is advisable that the resin (resin raw material) at least in the raw material stage has a high elastic modulus. If the elastic modulus of the resin is too low, the amount of deformation of the resin during molding will be too great, and the adhesion between the resin (especially the island parts) and the heat conductive particles (and thus the thermal conductivity of the composite material) may decrease.

[0035] The elastic modulus (Young's modulus) of the resin is preferably, for example, 0.1 GPa or more, 0.5 GPa or more, 1 GPa or more, 1.5 GPa or more, or even 2 GPa or more. The upper limit of the elastic modulus of the resin is, if daring to say, 15 GPa, 10 GPa, or even 5 GPa.

[0036] Since it is difficult to determine the elastic modulus of a resin during or after molding (composite material), the "elastic modulus" in this specification refers to the elastic modulus of the raw resin material unless otherwise specified. For the "elastic modulus," it is sufficient to adopt the nominal value listed in the catalog of the resin used. If no such nominal value is available, the elastic modulus of the resin can be determined using a viscoelasticity spectrometer.

[0037] The Young's modulus of typical resins is, for example, PMMA: 2.5 GPa, and olefin elastomer: <0.1 GPa.

[0038] 《Manufacturing method》 The composite material is obtained, for example, by molding a mixture of a thermally conductive particle (filler) raw material and a resin (matrix) raw material.

[0039] (1)Mixtures / raw materials The island-shaped portions may be formed during molding or during subsequent solidification, but it is preferable that granular resin that can become the island-shaped portions is already contained in the mixture (e.g., the resin raw material), which makes it easier to form the island-shaped portions.

[0040] The granular resin may be in the form of raw resin particles, or a part of the raw resin (for example, the surface layer) may be softened or melted. The mixture may be in a solid-liquid coexistence state (semi-molten state) in which the granular resin and the melted (including softened) resin are mixed. The size and ratio (solid phase rate) of the granular resin may be adjusted by controlling the heating temperature and heating time in consideration of the type of resin, softening point, melting point, etc. (heating step). For example, the heating temperature is 80 to 200°C, or 100 to 150°C, and the heating time is 0.1 to 1 hour, or 0.3 to 0.7 hours.

[0041] (2) Molding process By molding the mixture under pressure, it becomes easier to obtain a composite material with high thermal conductivity in which the thermally conductive particles are densely distributed among the islands of the resin. Molding can be performed by, for example, compression molding, extrusion molding, injection molding, transfer molding, etc.

[0042] The molding pressure (compressive force) applied to the mixture is, for example, 10 to 500 MPa, 50 to 400 MPa, or even 100 to 300 MPa. If the molding pressure is too low, a dense (high thermal conductivity) composite material cannot be obtained, and if the molding pressure is too high, productivity may decrease and costs may increase. The direction of application of the molding pressure may be adjusted to orient the thermal conductive particles in a specific direction. For example, in the case of BN particles, it is recommended to orient the surface direction of the BN particles so that it is approximately parallel to the heat flux direction of the composite material.

[0043] The molding step may be performed in multiple stages. For example, the molding step may include a first molding step of obtaining a molded body by pressure molding the mixture, and a second molding step of further pressure molding the molded body at a temperature equal to or higher than the softening point of the resin raw material. The first molding step may be performed without heating the mixture. The second molding step may be performed in accordance with the above-mentioned heating step.

[0044] (3) Supplementary Information The mixture may contain a coupling agent that enhances the affinity between the thermally conductive particles and the resin. The coupling agent may be introduced by surface treatment of the thermally conductive particles (coupling treatment, hydrophobic treatment, etc.), or may be added when mixing (kneading) the thermally conductive particles with the resin. Examples of the coupling agent include hexamethyldisilazane (HMDS: CH 19 There are silane coupling agents such as NSi2).

[0045] In addition to the thermally conductive particles, the composite may contain auxiliary particles with different materials, characteristics, particle sizes, etc. In the case where the thermally conductive particles are h-BN particles, the auxiliary particles may be, for example, c-BN particles, carbon particles (nanocarbon particles, graphite particles, diamond particles, etc.). The auxiliary particles may be smaller than the island-shaped portions, for example, like the thermally conductive particles. However, auxiliary particles larger than the island-shaped portions may also be included in the composite.

[0046] If the resin is a thermosetting resin, it is advisable to perform a heat hardening treatment (cure treatment) after molding. The composite material may be in the shape of the final product or a shape close to it, or it may be a material or intermediate material to be processed later.

[0047] 《Composite material》 The composite material is used, for example, in heat dissipation members, substrates, housings, etc. of electronic devices. Such a composite material may have high thermal conductivity and high specific resistance (electrical resistivity). The thermal conductivity of the composite material is, for example, 10 to 60 W / mK, 15 to 50 W / mK, or even 30 to 40 W / mK. The thermal conductivity is measured along the main heat flux direction or the orientation direction of the thermally conductive particles, unless otherwise specified. EXAMPLES

[0048] A number of samples (composite materials) made of thermally conductive particles and resin were produced, and the properties of each sample were evaluated. The present invention will be specifically described below with reference to the following examples.

[0049] [First Example] 《Raw materials》 (1) Thermally conductive particles As the thermally conductive particle source (raw material), commercially available h-BN powder (manufactured by Denka Co., Ltd.) and AlN powder (manufactured by Showa Denko K.K.) were used. Two types of h-BN powder with different particle morphologies (average aspect ratios) were prepared. The thermal conductivity (longitudinal / planar direction) of the BN particles was approximately 200 W / mK, and the thermal conductivity of the AlN particles was approximately 230 W / mK. The average aspect ratio of each particle will be described later.

[0050] (2) Resin As a resin raw material, granular (approximately spherical) polymethyl methacrylate (PMMA / simply referred to as "granular resin") was prepared as follows.

[0051] 2 g of polyvinyl alcohol (degree of polymerization: 2000) was added to 210 ml of water with stirring, and the temperature was raised to 90° C., after which it was dissolved over 1 hour.

[0052] After the solution was cooled to room temperature, it was transferred to a round-bottom flask equipped with a mechanical stirrer. 90 g of methyl methacrylate and 0.9 g of oil-soluble azo polymerization initiator (AIBN) were added to the solution, and stirring (stirrer rotation speed: 300 rpm) was continued for 30 minutes under a nitrogen stream. Reagents manufactured by Fujifilm Wako Pure Chemical Corporation were used for all raw materials.

[0053] The mixture was stirred under a nitrogen stream and held at 60°C for 1 hour, then held at 70°C for 10 hours to polymerize the monomer (methyl methacrylate). The treated product was allowed to cool to room temperature, filtered through a screen mesh, washed with water and methanol, and then vacuum dried. The residue was classified using a sieve with a mesh size of 500 μm, and 26 g of particles that passed through the sieve were collected. Each particle observed under a microscope was generally approximately spherical with a diameter of about 200 to 500 μm. The elastic modulus of this granular resin was 2.5 GPa. The elastic modulus was measured using a viscoelasticity spectrometer (manufactured by Iwamoto Seisakusho Co., Ltd.) as described above. The measurement conditions were as follows: sample: film-like (thickness: 0.5 mm, width: 5 mm, grip length: 10 mm), frequency: 10 Hz, temperature range: Rt to 200°C, and program speed: 10°C / min.

[0054] <<Manufacturing of Composite Materials>> For each thermally conductive particle, a composite material in which the shape of the granular resin partially remained (semi-molten) (referred to as an "unevenly distributed sample") and a composite material in which the shape had disappeared (referred to as a "uniform sample") were produced as follows.

[0055] (1) Unevenly distributed sample Each thermally conductive particle (filler) and the above-mentioned granular resin were weighed and mixed so that each thermally conductive particle accounted for 50 volume % of the total composite material. The mixed thermally conductive particles and granular resin were mixed manually.

[0056] The mixture was filled into a mold cavity (4 x 16 x 2 mm) and heated (mold temperature: 130°C for 30 minutes) (heating process). The heated mixture was cooled to room temperature while being pressurized (300 MPa) in one axial direction in the mold (molding process). The solidified material (composite material) was then removed from the cavity and used as the unevenly distributed samples (samples 1 to 3).

[0057] (2) Uniform sample The completely melted liquid resin and the thermally conductive particles were mixed by hand and then vacuum dried at room temperature for 24 hours. The mixture thus obtained was heated and molded in a mold in the same way as the unevenly distributed sample to obtain a uniform sample.

[0058] Observation and Measurement (1) SEM Each sample was cut out, filled with resin, polished, and the cross section was observed with a scanning electron microscope (SEM). These are shown in Figures 1A to 1C (collectively simply referred to as "Figure 1"). Each enlarged photograph in Figure 1 shows the area where thermally conductive particles are present.

[0059] (2) Average aspect ratio (AR) Based on the SEM images of each uniform sample, the aspect ratio of the thermally conductive particles (maximum length in the longitudinal direction / length in the direction perpendicular to the longitudinal direction) was measured and calculated, and the results are shown in Figure 2. The average aspect ratio thus obtained is shown as the AR value in each figure.

[0060] (3) Area ratio Image processing (software: ImageJ) was performed on the SEM images of each unevenly distributed sample, and the area ratio of each resin in the island and intervening parts to the whole was calculated. Each area ratio is also shown in each figure.

[0061] The area ratio of the island-like portion was calculated based on the basic region (440 μm × 630 μm). The area ratio of the intervening portion was calculated based on the enlarged region (50 μm × 50 μm) of the remaining region obtained by excluding the island-like portion from the basic region. Specifically, the image was binarized using ImageJ, and the area ratio of the black region was determined as the area ratio of the intervening portion, with the black region being the intervening portion and the white region being the filler.

[0062] (4) Thermal conductivity The thermal conductivity (λ) of each sample was determined by the nanoflash method. Specifically, the thermal conductivity was calculated as λ = α·Cp·D from the thermal diffusivity (α) measured by the nanoflash method (measurement device: NETZSCH LFA447), the specific heat (Cp) measured by a differential scanning calorimeter (DSC), and the density (D) calculated from the volumetric ratio of each material.

[0063] The thermal diffusivity of each sample was measured in a direction perpendicular to the direction of pressure applied during production. The thermal conductivity of each sample (in the thickness direction of the test piece) thus obtained is summarized in Figure 3.

[0064] [Second Example] (1) Preparation of samples A non-uniform distribution sample (sample 4) was also produced by replacing the PMMA used in the first embodiment with an olefin-based elastomer. The olefin-based elastomer used was OE-90 manufactured by M-Tech Chemical Co., Ltd. The elastic modulus was measured in the same manner as in the first embodiment and was found to be 0.1 GPa. The mixture of BN particles (AR=10) as thermally conductive particles and the olefin-based elastomer as granular resin was heated at a mold temperature of 130°C for 30 minutes (heating process). The other processes were carried out in the same manner as in the first embodiment.

[0065] (2) Observation and measurement The sample thus obtained was observed and measured in the same manner as in Example 1. The SEM image is shown in Figure 4A, and the thermal conductivity is shown in Figure 4B. Both figures are collectively referred to as "Figure 4."

[0066] [evaluation] As is clear from Figures 1, 3, and 4, all of the composites in which flat thermally conductive particles (BN particles) are unevenly distributed between the island-like parts of the resin exhibit high thermal conductivity (10 W / mK or more) even when the thermally conductive particles are about 50% by volume. In addition, as is clear from a comparison of Samples 1 and 2 (Figure 3) with Sample 4 (Figure 4B), composites using resins with a high modulus of elasticity also exhibit higher thermal conductivity.

[0067] [Consideration] (1) Morphology of thermally conductive particles As is clear from the comparison of Samples 1 and 2 with Sample 3 shown in Figure 3, the thermal conductivity of the composite material differed greatly depending on the morphology (average aspect ratio) of the thermally conductive particles, even among unevenly distributed samples. The reason for this is thought to be as follows. As shown in Figure 5, flat thermally conductive particles (AR >> 1) have a large area of ​​contact or proximity between adjacent particles. In this case, sufficient thermal conduction paths are easily formed between the thermally conductive particles. On the other hand, the area of ​​contact or proximity between adjacent particles is very small for roughly spherical thermally conductive particles (AR ≒ 1), and there are many gaps where resin is interposed. In this case, it is difficult for a thermal conduction path to be formed between the thermally conductive particles. Thus, it is thought that the thermal conductivity of the composite material differed greatly depending on the morphology of the thermally conductive particles, even among unevenly distributed samples.

[0068] (2) Island-like part As is clear from Sample 1 and Sample 2 shown in Figure 3, even if the thermal conductive particles are flat, the thermal conductivity of the composite material differs greatly depending on whether it is an unevenly distributed sample or a uniform sample. The reason for this is thought to be as follows. Even if the ratio of thermal conductive particles present in the entire composite material is the same, in an unevenly distributed sample with island-shaped parts, the thermal conductive particles (fillers) are closer to each other than in a uniform sample without island-shaped parts. If we explain it diagrammatically with reference to Figure 6, when the number of fillers is n, the filler width is f, the island width is p, and the filler intervals are d1 and d0, then d1 = d0 - 2p / n. In other words, considering the same size of area, in an unevenly distributed sample with island-shaped parts, the fillers are closer to each other by (2p / n) compared to a uniform sample without island-shaped parts, and the larger the island parts (p), the closer the fillers are to each other. Thus, even when flat thermal conductive particles are used, it is thought that the thermal conductivity differs greatly depending on the presence or absence of island-shaped parts.

[0069] (3) Type of resin As is clear from a comparison between Samples 1 and 2 shown in Fig. 3 and Sample 4 shown in Fig. 4B, even among the unevenly distributed samples, the thermal conductivity of Sample 4 was lower than that of Samples 1 and 2. This is thought to be due to the difference in the thermal conductivity of the resin itself.

[0070] However, sample 4 had higher elasticity than samples 1 and 2. For this reason, it is believed that the composite material (sheet, etc.) of sample 4 can also sufficiently reduce the thermal resistance between a heat-generating component (electronic device, etc.) and a heat-dissipating component (heat sink, etc.) when it is interposed between the two.

[0071] From the above, it was confirmed that according to the present invention, a composite material having excellent thermal conductivity can be obtained while suppressing the amount of thermally conductive particles.

Claims

1. A composite material comprising a resin and thermally conductive particles having a higher thermal conductivity than the resin, The resin has granular island portions and intervening portions between the island portions, the island portion and the intermediate portion are made of the same type of resin, The interposed portion is 1 to 10% of the total cross-sectional area of ​​the composite material, The thermally conductive particles are unevenly distributed between the island portions and are a composite material containing BN particles made of hexagonal boron nitride.

2. The composite material of claim 1 , wherein the thermally conductive particles are flat or fibrous.

3. 3. The composite material according to claim 1, wherein the thermally conductive particles account for 5 to 70% by volume of the entire composite material.

4. 4. The composite material according to claim 1, wherein the island-shaped portions occupy 30 to 80% of the total cross-sectional area of ​​the composite material.

5. The composite material according to any one of claims 1 to 4, wherein the island-shaped portions are larger than the thermally conductive particles.

6. A composite material described in any of claims 1 to 5, wherein the interposed portion accounts for 2 to 8% of the total cross-sectional area of ​​the composite material.

7. A composite material as described in claim 6, wherein the interposed portion accounts for 3 to 6% of the total cross-sectional area of ​​the composite material.

8. A composite material as described in claim 7, wherein the interposed portion accounts for 4 to 5% of the total cross-sectional area of ​​the composite material.

9. 9. The composite material according to claim 1, wherein the resin is made of a resin raw material having an elastic modulus of 0.1 GPa or more.

10. The composite material according to any one of claims 1 to 9, wherein the resin comprises polymethylmethacrylate (PMMA) or an olefin-based elastomer.

11. A molding process is provided for pressurizing a mixture of a resin raw material and a thermally conductive particle raw material, A manufacturing process which gives rise to a composite material according to any one of claims 1 to 10.

12. The method for producing a composite material according to claim 11, wherein at least a part of the resin raw material is in a granular form.

13. The method for producing a composite material according to claim 11 or 12, wherein the resin raw material has an elastic modulus of 0.1 GPa or more.

14. The method for producing a composite material according to any one of claims 11 to 13, wherein the molding step further comprises pressurizing the mixture to form a molded product at a temperature equal to or higher than the softening point of the resin raw material.

Citation Information

Patent Citations

  • Insulation heat radiation film and method for producing the same

    JP2012144638A

  • Heat conductive material

    JP2013194223A

  • Composite material and production method thereof

    JP2015096587A

  • JP2016-255055A

  • Thermally conductive material

    JP2016204653A